Sovereignty : European and Global Histories, 1400-1800 - Lee, Daniel,; Zwierlein, Cornel, (Early Modern History and Modern History E-Books Online, Collection 2024., 2025)
Was the emperor as sovereign allowed to seize the property of his subjects? Was this handled differently in late medieval Roman law and in the practice and theory of zabt in Mughal India? How is political sovereignty relating to the church´s powers and to trade? How about maritime sovereignty after Grotius? How was the East India Company as a ´corporation´ interacting with an Indian Nawab? How was the Shogunate and the emperor negotiating ´sovereignty´ in early modern Japan? The volume addresses such questions through thoroughly researched historical case studies, covering the disciplines of History, Political Sciences, and Law. Contributors include: Kenneth Pennington, Fabrice Micallef, Philippe Denis, Sylvio Hermann De Franceschi, Joshua Freed, David Dyzenhaus, Michael P. Breen, Daniel Lee, Andrew Fitzmaurice and Kajo Kubala, Nicholas Abbott, Tiraana Bains, Cornel Zwierlein, Mark Ravina.